Potensi Antijamur Ekstrak Metanol Daun Mangrove Rhizopora Mucronata Terhadap Jamur Candida Albicans Dan Aspergillus Niger - Usman Usman; Vega Julia Putri Adi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
Candida Albicans and Aspergillus Niger are some of the infectious fungi. Empirically bark, flower, root and mangrove leaves Rhizophora mucronata can be a hepatitis drug. This study aims to determine the antifungal potential of methanol extract of Rhizophora mucronata leaves to Candida Albicans and Aspergillus Niger fungus. Chemical test results that have been done previously are alkaloids, Flavanoid , triterpenoids, saponins, tannins and hydroquinone phenols. The antifungal test was performed by agar diffusion method on Potatos Dextrose Agar (PDA) medium and paper disc.Paper disc soaked in methanolic extract of Rhizophora mucronatapada leaf concentration 1000 ppm, 800 ppm, 600 ppm, 400 ppm and 200 ppm. The positive control solution used ketokenazole drug and negative control using aquades with incubation period of 3 x 24 hours. The results did not prove that Rhizophora mucronata leaf methanol extract was effective to inhibit antifungal activity against Candida Albicans and Aspergillus Niger fungi.